2012
DOI: 10.1158/0008-5472.can-11-2373
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 and ROCK2 Are Required for Non-Small Cell Lung Cancer Anchorage-Independent Growth and Invasion

Abstract: Evidence is emerging that the closely related ROCK1 and ROCK2 serine/threonine kinases support the invasive and metastatic growth of a spectrum of human cancer types. Therefore, inhibitors of ROCK are under preclinical development. However, a key step in their development involves the identification of genetic biomarkers that will predict ROCK inhibitor anti-tumor activity. One identified mechanism for ROCK activation in cancer involves the loss of function of the DLC1 tumor suppressor gene, which encodes a GT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 36 publications
7
106
0
Order By: Relevance
“…Increased RhoA activation and signaling through its downstream effectors, such as Rho-associated kinase (ROCK), contributes to cancer progression. Activation of the RhoA-ROCK signaling axis initiates cytoskeletal changes that are essential for cancer cell motility and invasion, initiates gene transcription, and promotes cancer cell proliferation (Yagi et al, 2011;Vigil et al, 2012;Zhang et al, 2013). It is currently unknown if GRPR-mediated RhoA-ROCK signaling plays a role in regulation of colon cancer cell migration.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Increased RhoA activation and signaling through its downstream effectors, such as Rho-associated kinase (ROCK), contributes to cancer progression. Activation of the RhoA-ROCK signaling axis initiates cytoskeletal changes that are essential for cancer cell motility and invasion, initiates gene transcription, and promotes cancer cell proliferation (Yagi et al, 2011;Vigil et al, 2012;Zhang et al, 2013). It is currently unknown if GRPR-mediated RhoA-ROCK signaling plays a role in regulation of colon cancer cell migration.…”
Section: Abbreviationsmentioning
confidence: 99%
“…It has been well established that ROCK1 is involved in the reorganization of the actin cytoskeleton, which is important in cell migration and invasion (17)(18)(19). In addition, the expression levels of ROCK1 were reported to be significantly upregulated in multiple types of human cancer, including bladder (14), prostate (20) and lung (21) cancer, suggesting that ROCK1 acts as an important oncogene in multiple types of cancer. A previous study investigated the role of ROCK1 in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they fail to block cell migration completely. Recent studies reported the development of several new ROCK inhibitors, including, OXA-06 and RKI-18, which showed good potency against ROCK in vitro and in cells (14,15). However, the OXA-06 compound has poor pharmacokinetic properties for use in vivo (14) and no in vivo data for RKI-18 were reported (15).…”
Section: Introductionmentioning
confidence: 99%